From Bayt al-Hikmah to Algebra: The Intellectual Legacy of the Islamic Golden Age - Rahman, Habibur; Sudirman, Sudirman (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
The Islamic Golden Age occurred between the 8th and 14th centuries, a period when knowledge in the Islamic world reached its zenith. During this time, Muslim scientists, philosophers, and scholars made significant contributions to various fields of knowledge, such as mathematics, astronomy, medicine, and philosophy. Key figures in the development of science included Al-Khwarizmi, who pioneered algebra, and Ibn Sina, who authored the medical encyclopedia Al-Qanun fi al-Tibb (The Canon of Medicine). Great libraries and universities, such as the Bayt al-Hikmah (House of Wisdom) in Baghdad, served as intellectual hubs that attracted scholars from across the globe. However, this progress eventually slowed due to factors such as the Mongol invasions, political fragmentation, and the rise of Europe. The scientific legacy of the Islamic Golden Age remains relevant and influential in the history of global knowledge, highlighting the pivotal role of Islamic civilization in advancing human intellectual endeavors.